THE EFFECT BETWEEN DIABETES MELLITUS DIABETES AMONG CHANGES BLOOD SUGAR LEVELS AT Dr. H. MARZOEKI MAHDI HOSPITA BOGOR: PENGARUH ANTARA SENAM DIABETES MELLITUS TERHADAP PERUBAHAN KADAR GULA DARAH PADA PENDERITA DIABETES MELLITUS DI RUMAH SAKIT Dr. H. MARZOEKI MAHDI KOTA BOGOR - Harun Harun Al Rasid; Ami Ami Oetami Wiharjo (Jurnal Ilmiah Wijaya, 2018)
In 2012 diabetes mellitus is the cause of death from 1,5 million (WHO,2016). The population of diabetes mellitus (DM) in indonesia is currently ranked fifth in tyhe world. In 2013 people with diabetes mellitus in the homeland reaches 8.554.155 people. The continuous increase in the number of patients with diabetes mellitus and the magnitudeof the cost of treatment due to complications, then the best effort is prevention. Exercise of physical exercise is an early attempt to prevent, control, and overcome diabetes. Type of Quasi Experimenta research with Non Randomited Pretest and Posttest Control Group Design methods. Research location in RS Dr. H. Marzoeki Mahdi dated 26 April 2017 number of sample counted 32 respondents with diabetes mellitus with sample Purposive Sampling. Tools used in date collection are Accu-Chek Akctive and observation sheet. Technique of date analysis is bivariate analysis with SPSSM program. The influence of diabetes mellitus gymnastics on changes in blood sugar levels in Dr. H. Marzoeki Mahdi Hospital in 2017. The ntervention group of blood sugas levels before gymnastics and after gymnastics decreased 24,69 mg/dL, in the control group of blood sugar levels on the first day and the fourth day increased 10,56 mg/dL. Statistical test results using Independent T Test obtained P value = 0,000 which means P value <0,05 means the influence of diabetes gymnastics to changes in blood sugar levels in people with diabetes mellitus in Dr. H. Marzoeki Mahdi Hospital. This research is expected